New information on the forearm and manus of Ceratosaurus nasicornis Marsh, 1884 (Dinosauria, Theropoda), with implications for theropod forelimb evolution. Issue 2 (3rd March 2016) - Carrano, Matthew T.; Choiniere, Jonah
ABSTRACT: Here we describe the forearm and manus of the ceratosaurian theropod dinosaur Ceratosaurus nasicornis Marsh, 1884, from the Upper Jurassic Morrison Formation of the western U.S.A. Recently removed from exhibition and reprepared, the holotype offers important new information on the morphology of this taxon that bears on the evolution of the forelimb in nonavian theropod dinosaurs more generally. The ulna and radius show particular similarities to those of Dilophosaurus and Eoabelisaurus but lack features that characterize derived abelisaurids. In the manus, Ceratosaurus bears short first phalanges, like more derived taxa in the clade, but retains metacarpals that are much more similar to those of Dilophosaurus, Berberosaurus, and Eoabelisaurus . Taken together, and incorporated with existing phylogenetic data on other ceratosaurs, these data are consistent with the placement of Ceratosaurus as close to Abelisauroidea but basal to Eoabelisaurus . More importantly, they strongly imply that the extremely reduced manus of Limusaurus is a derived condition that does not reflect the primitive state for Ceratosauria and therefore that Averostra is not the most likely placement for a shift in manus digit identity during theropod evolution. Finally, digit reduction began in ceratosaurs that still possessed most phalanges and unguals, and we infer that grasping would have been retained as a primary, if reduced, function in these forms. Citation for this article: Carrano, M. T., and J. Choiniere. 2016. New information on the forearm and manus of Ceratosaurus nasicornis Marsh, 1884 (Dinosauria, Theropoda), with implications for theropod forelimb evolution. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1054497.